Pengaruh Investasi Terhadap Penyerapan Tenaga Kerja di Indonesia - Mustika, Nelda; Khairani, Amelia Khairani (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze the effects of Domestic Investment (PMDN), Foreign Direct Investment (FDI), economic growth, and wages on labor absorption in Indonesia. The study utilizes panel data from 34 provinces in Indonesia over the period 2020–2024, employing the Random Effect Model (REM) approach. The results indicate that PMDN has a positive and significant effect on labor absorption, while FDI has a positive but non-significant effect. Economic growth is found to have a negative and significant impact on labor absorption, whereas wages exert a negative and significant effect. These findings highlight the crucial role of domestic investment in job creation, while suggesting that wage policies and economic growth need to be managed carefully to avoid hindering labor absorption. The study provides important implications for the formulation of economic and labor policies that support sustainable and optimal employment generation.